Molecular modelling and in vitro studies of Daruharidra as a potent alpha-amylase inhibitor - Bhatnagar A.; Saini R.; Dagar P.; Mishra A. (My University, 2025)
The present study aims at exploring the potential of the Daruharidra plant (stem and bark) for inhibition of alpha-amylase. Aqueous and ethanolic extraction yielded the highest total phenolic content (TPC) of 101.4 and 111.8 mcg of gallic acid equivalent. Methanol and ethanol extract had Total flavonoid content (TFC) of 319.6 and 288.3 mcg of quercetin equivalent, respectively. In contrast, petroleum ether extraction resulted in the lowest TPC of 23.6 and TFC of 8.33 mcg, respectively. Methanol (5.554 mg/ml), acetone (6.576 mg/ml), and ethanol (7.321 mg/ml) extract had the lowest IC50 values in alpha-amylase inhibition with the mode of inhibition being non-competitive inhibition. HR-LCMS was used for comprehension of phytoconstituents present in the extract. Amongst hundreds of hits observed 10 ligands of alkaloid nature were used for docking studies. Berbamine, alloxanthine, protopine and benazepril along with reference molecule (Acarbose) were subjected to Molecular dynamics (MD) simulation to analyze the stability of the docked protein-ligand complex. The values of RMSD, RMSF, RG, H-Bond and SASA, the interaction energy of all protein-ligand complexes were calculated after 150 ns of MD simulation. The results of screened complexes revealed good stability as compared to reference Acarbose. These screened ligands used for simulation have the most negative binding energies that interacted with alpha amylase enzyme having −9.28 kcal/mol, −7.51 kcal/mol, −7.73 kcal/mol and −8.00 kcal/mol, energies respectively. The results show significant alpha-amylase inhibitory activity and interaction of ligands targeting this enzyme, which can be used for cross-validation, in vitro Communicated by Ramaswamy H. Sarma. © 2022 Informa UK Limited, trading as Taylor & Francis Group.